THE PROCESS OF OBTAINING A FUEL BRIQUETTE BASED ON OIL SLUDGE, GOSSYPOL RESIN AND LIQORICE ROOT (Scientific journal of the Fergana State University, 2024)
Samples of fuel briquettes were obtained based on oil sludge, gossypol resin, quicklime and spent licorice root. Fuel briquettes are tested to determine mechanical strength. The results of testing samples of fuel briquettes during compression, dropping and abrasion are presented. It has been proven that the mechanical strength indicator of the FB-4 fuel briquette sample is the best than other samples.